2017
DOI: 10.1186/s13059-017-1221-3
|View full text |Cite
|
Sign up to set email alerts
|

The histone H3 variant H3.3 regulates gene body DNA methylation in Arabidopsis thaliana

Abstract: BackgroundGene bodies of vertebrates and flowering plants are occupied by the histone variant H3.3 and DNA methylation. The origin and significance of these profiles remain largely unknown. DNA methylation and H3.3 enrichment profiles over gene bodies are correlated and both have a similar dependence on gene transcription levels. This suggests a mechanistic link between H3.3 and gene body methylation.ResultsWe engineered an H3.3 knockdown in Arabidopsis thaliana and observed transcription reduction that predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 60 publications
(75 reference statements)
11
142
0
1
Order By: Relevance
“…Subsequent activity of CAF‐1 independent nucleosome assembly mechanisms re‐establishes wild‐type‐like nucleosome occupancy in most of the genome, as seen in the resting cells of leaves (Munoz‐Viana et al ., ). Second, H3.3 limits H1 recruitment and thus favors DNA methylation (Wollmann et al ., ). The shifted H3.1‐H3.3 balance in CAF‐1 mutants is thus expected to lead to reduced H1 presence and increased CHG methylation, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent activity of CAF‐1 independent nucleosome assembly mechanisms re‐establishes wild‐type‐like nucleosome occupancy in most of the genome, as seen in the resting cells of leaves (Munoz‐Viana et al ., ). Second, H3.3 limits H1 recruitment and thus favors DNA methylation (Wollmann et al ., ). The shifted H3.1‐H3.3 balance in CAF‐1 mutants is thus expected to lead to reduced H1 presence and increased CHG methylation, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The particular pattern of DNA methylation in the CG context located between the transcription start site (TSS) and transcription termination site (TTS) of genes present in angiosperms is referred to as gene body methylation (gbM) (Bewick & Schmitz, ). In Arabidopsis, gbM is linked to a relative enrichment in linker histone H1 and histone variant H3.3 (Wollmann et al ., ) and most of the genes affected in H3.3 knockdown alleles correspond to genes involved in either environmental response or development. Interestingly, there is also evidence that loss of function in the increase in bonsai methylation 1 ( IBM1 ) gene affects gbM negatively, replacing CG methylation with CHG methylation and H3K9me2 (Saze et al ., ).…”
Section: Maintenance and Removal Of Dna Methylationmentioning
confidence: 99%
“…Study of the histone mutation in chondroblastoma indicated that p.Lys36Met alteration predominantly occurred in H3F3B gene in majority of the chondroblastoma cases, whereas p.Gly34Trp mutations are dominated in the H3F3A gene [9]. As the histone H3 variant H3.3 is able to regulate the patterns of DNA methylation at the gene body [10], it is possible that the mutated H3.3 in chondroblastic initially alters DNA methylation status and further leads to the development of chondroblastoma in patients. In mammals, since DNA methyltransferases (DNMTs) and some histone modifiers, including H3K9 methyltransferases G9a and GLP, are essential for the establishment and maintenance of DNA methylation at heterochromatin loci [11,12] investigation the interact of H3.3 and the above enzymes might create a novel direction for understanding the genesis and progression of chondroblastoma.…”
Section: Chondroblastomamentioning
confidence: 99%